People, predicaments and potentials in Africa - Ochiai, Takehiko; Hirano-Nomoto, Misa; Agbiboa, Daniel E. (African potentials (Series), 2021)
"The term 'African Potentials' refers to the knowledge, systems, practices, ideas and values created and implemented in African societies that are expected to contribute to overcoming various challenges and promoting people's wellbeing. This collection of articles, focused on African societies, is based on the idea that 'Africa is People'. In this book, African people are placed at the centre of the discussion. The book's contributors, all of whom believe in African people and their potentials, consider women, minors and young people, people with disabilities, entrepreneurs, herders, farmers, mine workers, refugees, migrants, traditional rulers, militiamen and members of the political elite, and examine their predicaments and potentials in detail. Africa is people, and African potentials can be found only in African people themselves."--Publisher.